TRACES OF THE MARINE MJøLNIR IMPACT EVENT - Dypvik H.; Salvigsen O.; Kalleson E.; Smelror M.; Sandbakken P.T. (My University, 2006)
The sediments of the Barents Sea region carry geological information reflecting the influence of the Mjølnir impact event at the Volgian-Ryazanian boundary, even in remote locations without any direct macroscopic geological and paleontological evidence. The ejecta distribution in the area was probably highly asymmetrical, but geological and related geochemical and paleontological signals in the sediments show the environmental consequences of the impact (e.g., impact generated waves, tsunami, currents, changing redox conditions) to be more symmetrically distributed. The influences of the asteroid impact are seen in the distributional anomalies (Ir, Th, U, Ni, Cr and prasinophycean algae of the genus Leiosphaeridia) of studied cores from 30 to 500 km away from the crater. A core from about 800 km southwest of the crater carries no obvious direct evidence of the impact. This study shows that additional geological parameters other than, e.g., shocked quartz, spherules, Ir-anomalies, may carry information indicating possible environmental impact influence even more than 10 crater diameters away from the impact site. © 2006 Elsevier B.V. All rights reserved.
Keywords: ENVIRONMENTAL EFFECTS; MICROFLORA; MJøLNIR IMPACT; TRACE ELEMENTS